Kajian Perencanaan Ruang Terbuka Hijau Privat pada Rusunawa dan Rusunami di Jakarta Timur - Reasista, Dezni; Nasrullah, Nizar; Budiarti, Tati (Jurnal Lanskap Indonesia, 2026)
The rapid growth of vertical housing in East Jakarta presents significant challenges in providing adequate private Green Open Space (GOS). This study aims to develop planning strategies for GOS in Rusunawa Jatinegara Barat and Rusunami Samawa Pondok Kelapa by analyzing existing site conditions, oxygen requirements, water supply potential, microclimate conditions, and residents’ perceptions. Data were collected through site observations, structured questionnaires distributed to 100 respondents using the Slovin formula, in-depth interviews, and document reviews. The analysis indicates that the oxygen demand, estimated at 0.864 kg/person/day, is far from being met; the existing vegetation only contributes about 9–10% of the total need, with daily oxygen production reaching approximately 2,714.97 kg/day in Rusunami Samawa Pondok Kelapa and 2,413.6 kg/day in Rusunawa Jatinegara Barat. The calculated GOS requirement for clean water recharge highlights an ideal green space area of around 16.95 ha for Rusunawa Jatinegara Barat and 73.91 ha for Rusunami Samawa Pondok Kelapa. The Temperature Humidity Index (THI) analysis shows an index score exceeding 27, indicating thermal discomfort due to the lack of adequate shading vegetation. The recommended planning strategies focus on optimizing the site’s green design by increasing the proportion of wide-canopy trees, dense shrubs, and ground covers, as well as implementing integrated rainwater harvesting systems, biopores, and green corridors to enhance natural cross-ventilation. This study emphasizes the importance of participatory approaches and policy integration into local RTRW/RDTR frameworks to ensure the sustainability of private green open spaces in vertical housing developments.